Study on Paradigm Shift in Social Science Research (Okhaldhunga Journal, 2026)
Social science research provides the rationalization of social behavior by relying on the belief that its causes better known and measurable. The research aims to find laws and postulate theories for scientific knowledge meant for explaining natural or social phenomena. Within the field of social science research, many philosophical approaches are possible; but, in step with the authors, additional extreme approaches are often delimiting. solely arbitrator. This study aims to explore the emerging trends in social sciences research. The methodological approach of this research is based on the desk review known as a literature review or secondary research, includes a systematic analysis and synthesis of existing academic studies. Academic literatures were retrieved from Google Scholar. Relevant institutional and policy documents were also included where applicable. Peer-reviewed journal articles, academic books and well-regarded research reports published in English language were included in this study. Studies with weak methodological rigor, limited relevance to the review scope, duplicate records, and those lacking full-text availability were excluded from the final selection. Pragmatic studies become a very powerful way of the transformative research problem. By incorporating new approaches like Arts-based research, studies on paradigm shifts can be more transformative. This study concluded the blend of literary genres, new ways of thinking, and different quality standards provides a powerful framework for professional development that goes beyond traditional research methods.